APLIKASI DIAGNOSIS PENYAKIT DIABETES MELITUS MENGGUNAKAN METODE FUZZY MULTI CRITERIA DECISION MAKING - Indah Lestari Sumitro; Ika Purwanti Ningrum; Rahmat Ramadhan (Informatics Engineering Department of Halu Oleo University, 2016)
Fuzzy Multi Criteria Decision Making (FMCDM) can be seen as MCDM (Multi Criteria Decision Making) with fuzzy data. Fuzzy data can be applied for every alternatives or level of importance in every criterion. Every criteria or indications and kind of disease alternatives usually contains unpredictable values that prediction which given by decision maker done by qualitative and represented linguistically. This research aims to help the decision maker to determine category of Diabetes Mellitus (DM) which suffered from each categories of DM which related to indications that being determined. The system created by taking some categories of DM as data which will be used in calculation. The experiment that used the confusion matrix method resulted the values of accuracy is 100%, sensitivity is 100% and specificity is ∞ (infinite). The output of this system is alternatives of this diseased which Normal or undetected of DM, Pradiabetes, DM type 1, and DM type 2. Keywords— Confusion Matrix, Diabetes Melitus, Fuzzy Multi Criteria DecisionMaking.